2020
DOI: 10.1155/2020/3738673
|View full text |Cite
|
Sign up to set email alerts
|

Low Utilization of Partograph and Its Associated Factors among Obstetric Care Providers in Governmental Health Facilities at West Shoa Zone, Central Ethiopia

Abstract: Background. Globally, prolonged and obstructed labors were among the common causes of maternal morbidity and mortality in low- and middle-income countries including Ethiopia. The World Health Organization (WHO) recommends the routine use of partograph as a key intervention to avoid prolonged and obstructed labor. Despite the recommendation, studies indicated that the partograph utilization among obstetric care providers (OCPs) is still low. Therefore, this study is aimed at assessing the level of utilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 27 publications
6
31
1
Order By: Relevance
“…But it is lower than simiar study conducted in Tigray, Oromia and SNNPRE [ 10 14 , 16 ]. However, this finding was higher than a similar study conducted in cameron, Nigeria and West Shoa zone of oromia [ 6 , 8 , 9 ]. These differences could be due to the socio-political and economic differences of the studied area and also due to professional differences as indicated in some studies, only midwifery caregivers were studied [ 7 , 11 ].…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…But it is lower than simiar study conducted in Tigray, Oromia and SNNPRE [ 10 14 , 16 ]. However, this finding was higher than a similar study conducted in cameron, Nigeria and West Shoa zone of oromia [ 6 , 8 , 9 ]. These differences could be due to the socio-political and economic differences of the studied area and also due to professional differences as indicated in some studies, only midwifery caregivers were studied [ 7 , 11 ].…”
Section: Discussioncontrasting
confidence: 71%
“…According to different studies done in Ethiopia the magnitude of the utilization of partograph shown to have a wide variation from region to region and across zones of the same region [ 9 18 ]. Studies from the Central and Eastern zone of Tigray regional state reported the highest level of utilization from around 70 to 83 % [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its global acceptance, utilisation and correct completion rates as low as 31 and 3%, respectively, have been reported. 4 Following the update of its global recommendations on intrapartum care in 2018, 5 the WHO initiated a process to revise the partograph in light of recent evidence, including a new understanding of the individual variability of the progress of labours resulting in good perinatal outcomes, and the fact that many women do not experience a labour that conforms to the average rate on which the partograph design was based. 6,7 A large study and corresponding systematic reviews published in this journal [8][9][10] and subsequent analysis 11 failed to find evidence to support the use of a cervical dilatation rate of 1 cm/hour as a screening tool to predict adverse labour outcomes.…”
mentioning
confidence: 99%